Post a New Question


posted by .

perform indicated operations.

(a+3)/5(a+5)-(a-1)/3(a+5)=(a+3)5(a+5)/5(a+5)3(a+5)-(a-1)5(a+5)/5(a+5)3(at5)= 5a^2+25a+15a+75+5a^2+25a-5a-25/5(a+5)3(a+5)
i got (10a^2+60a-50)/5(a+5)3(a+5)and that's wrong. where did i go wrong?

  • math -



    Aside from that, I'd not include (a+5) twice, making it

    =3(a+3)/15(a+5) - 5(a-1)/15(a+5)
    = (3a+9-5a+5)/15(a+5)
    = 2(7-a)/15(a+5)

  • math -

    Since the a+5 is already common, you don't need it twice
    LCD = 15(x+5)
    so your second line
    = 3(a+3)/(15(a+5)) - 5(a-1)/(15(a+5))
    = (3a+9 - 5a + 5)/(15(a+5))
    = (-2a + 14)/(15(a+5))

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question